Riverine communities and waterborne diseases in South Eastern Nigeria - Oranye NO,; Utharas A,; Nora A, (Penerbit UKM, 2009)
Waterborne diseases (WBDs) have continued to be a major health threat to people living in many underdeveloped countries due to absence of basic infrastructure, especially water and health care facilities. In this study we report the findings of an investigation into waterborne diseases amongst the riverine communities in Anambra State, South Eastern Nigeria. A survey of 1200 heads of household using a questionnaire and 600 hospital records were reviewed. A major concern of the study was to identify socio-economic and cultural factors that drive the epidemiology of such diseases. Findings revealed significant differences in the prevalence of waterborne diseases within and between the communities, implicating education levels of the head of household, occupation, and source of water used. The study recommends the provision of community health education through trained community health workers and provision of functional and accessible health care services as a primary means of combating water borne diseases.